Exploring Mothers' Decisions on Exclusive Breastfeeding in Sario, Manado: A Qualitative Study - Angelia Pondaa; Cicilia Karlina Lariwu (Universitas Pahlawan Tuanku Tambusai, 2026)
Exclusive breastfeeding is an important strategy to improve maternal and child health; however, its practice is influenced by multiple complex factors. This study aimed to explore mothers’ decision-making processes regarding exclusive breastfeeding in Sario, Manado. A qualitative descriptive exploratory design was used. Data were collected through in-depth interviews with seven mothers (RS1–RS7) selected by purposive sampling. The study was conducted in May 2016 in the working area of Sario Community Health Center and analyzed using thematic analysis. The findings revealed four main themes: maternal knowledge and perception of exclusive breastfeeding, family and husband support, work and daily activities, and cultural and social influences. Mothers with better knowledge and stronger family support were more likely to practice exclusive breastfeeding, while insufficient knowledge, lack of family support, work-related constraints, and social influences including formula milk promotion were major barriers. In conclusion, exclusive breastfeeding decision-making is a complex process shaped by individual and contextual factors. Strengthening maternal education, family involvement, and workplace support is recommended.